Smartphone Use Does Not Have to Be Rude: Making Phones a Collaborative Presence in Meetings - Böhmer, Matthias; Saponas, Scott; Teevan, Jaime (ACM - Association for Computing Machinery, 2013)
Our personal smartphones are our daily companions, coming with us everywhere, including into enterprise meetings. This paper looks at smartphone use in meetings. Via a survey of 398 enterprise workers, we find that people believe phone use interferes with meeting productivity and collaboration. While individuals tend to think that they make productive use of their own phones in meetings, they perceive others as using their phones for unrelated tasks. To help smartphones create a more collaborative meeting environment, we present an application that identifies and describes meeting attendees. We deploy the application to 114 people at real meetings, and find that users value being able to access information about the other people in the room, particularly when those people are unfamiliar. To prevent users from disengaging from the meeting while using their phones, we employ a gaming approach that asks trivia questions about the other attendees. We observe that gameplay focuses attention within the meeting context and sparks conversations. These findings suggest ways smartphone applications might help users engage with the people around them in enterprise environments, rather than removing them from their immediate social context.